Amniotic membrane transplantation in a 2-month-old infant with toxic epidermal necrolysis - Abdelrahman M. Elhusseiny, MD; Ryan Gise, MD; Christina Scelfo, MD; Iason S. Mantagos, MD, PhD (American Journal of Ophthalmology Case Reports, 2021)
Purpose: To report a case of 2-month-old boy with Stevens-Johnson syndrome (SJS)/Toxic epidermal necrolysis (TEN) and ocular involvement that was successfully treated with cryopreserved amniotic membrane transplantation (AMT). Observation: A 2-month-old otherwise healthy boy was referred to Boston Children's Hospital with extensive rash and desquamation concerning for SJS/TEN. A skin biopsy was performed which showed full-thickness epidermal necrosis. AMT was performed at the bedside under general anesthesia. A combination of tobramycin and dexamethasone ointment was prescribed four times per day. On reassessment two weeks following AMT, the entire ocular surface had healed with no signs of conjunctival and/or corneal inflammation or ulceration. Conclusion and importance: To the best of our knowledge, our case represents the youngest patient with SJS/TEN to be managed by AMT and one of very few cases where acetaminophen is suspected to be the offending agent. This case highlights the efficacy of AMT at such a young age and feasibility of performing the procedure at bedside in these patients It also highlights that SJS/TEN can develop at such young age.